Drill & practice and modified Moore strategies: inference on students' mathematical deductive reasoning abilities - Kodirun, Kodirun; Busnawir, Busnawir (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: The effectiveness of learning strategies plays a pivotal role in enhancing the educational experience, engaging students, and ensuring comprehension of the subject matter.Aim: The primary objective of this research is to evaluate the comparative effectiveness of the modified moore method versus drill & practice strategies in facilitating student understanding and interest in logic and sets material.Method: Employing a quasi-experimental design, this investigation involved two groups of students enrolled in the 2022.1. Linear Algebra course, with 47 participants in one group and 52 in the other. Selection of participants was conducted purposively. Data collection was achieved through examinations and analyzed utilizing descriptive statistics along with the t-test.Result: Analysis revealed no significant difference in educational outcomes between students instructed using the modified moore method and those engaging with drill & practice. This lack of disparity was consistent across students with varying levels of proficiency in Logic and Sets, with the exception of the intermediate group. Within this specific cohort, individuals receiving instruction via drill & practice outperformed their counterparts experiencing the modified moore method.Conclusion: For students of intermediate skill levels, the drill & practice strategy proves to be more advantageous. The findings suggest that while both methods offer comparable benefits for students at different proficiency levels, the drill & practice approach may be more effective for enhancing the learning experience of those with moderate abilities in logic and sets.